2004
DOI: 10.1111/j.1523-1755.2004.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis-associated hypotension as an independent risk factor for two-year mortality in hemodialysis patients

Abstract: These results suggest that intradialysis hypotension and orthostatic hypotension after hemodialysis are significant and independent factors affecting mortality in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
462
2
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(495 citation statements)
references
References 13 publications
10
462
2
11
Order By: Relevance
“…Some authors suggested that glaucoma patients with an exaggerated nocturnal reduction in systemic arterial pressure have an altered OPP outside the period of arterial pressure reduction, which is possibly related to a general vascular dysregulation (27) . In addition to a circadian rhythm for arterial pressure where we observe a nocturnal fall, we also have some situations during the HD session in which we see a reduction in the average arterial pressure value (4)(5) . Therefore, there is hypotension during the HD session.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors suggested that glaucoma patients with an exaggerated nocturnal reduction in systemic arterial pressure have an altered OPP outside the period of arterial pressure reduction, which is possibly related to a general vascular dysregulation (27) . In addition to a circadian rhythm for arterial pressure where we observe a nocturnal fall, we also have some situations during the HD session in which we see a reduction in the average arterial pressure value (4)(5) . Therefore, there is hypotension during the HD session.…”
Section: Discussionmentioning
confidence: 99%
“…More serious complications include cardiac arrhythmia, convulsion, gaseous embolism, and intracranial hemorrhage (3) . Arterial hypotension still represents a major complication resulting from HD therapy; it frequently shortens the duration of dialysis and increases patient mortality rates (4)(5) . The pathogenesis of hemodynamic instability in response to fluid removal probably involves many factors such as defective plasma refilling (6) , abnormal body heating (7)(8) , an imbalance between endothelin and nitric oxide synthesis (9) , and defective adjustment of arteriovenous tone in response to the changes in the effective plasma volume (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Stefánsson et al found patients with IDH to be younger, more likely to be male, and to have similar comorbid cardiovascular disease burdens to patients without IDH. By contrast, other studies found patients with IDH to be older, more likely to be female, and more likely to have cardiovascular comorbid conditions compared with patients without IDH (19,20). In addition, without time sequence data, we cannot exclude the possibility that therapeutic responses like blood flow reduction and early dialysis termination were initiated for reasons other than hemodynamic instability (e.g., faulty vascular access), potentially altering the associations.…”
mentioning
confidence: 62%
“…Furthermore, the authors did not account for several potential confounding variables including hemoglobin (21), albumin (19,20), and low predialysis BP (20,21). Although multivariable models included a variable for uncontrolled hypertension, defined as mean predialysis BP.140/90 or mean postdialysis BP.130/85, this dichotomous term does not account for the U-shaped association of BP and outcomes (22).…”
mentioning
confidence: 99%
“…Chronic volume overload in ESRD has since time been recognized as the main responsible of hypertension development, with its detrimental role in increasing incidence of cardiovascular disease [1,2]. Moreover, HD-induced volume depletion is related to intradialityc hypotension [3], an independent risk factor for fatal events in ESRD population [4]. Definition of real volume overload before HD session may therefore represent a key point for minimizing complications and optimize treatment.…”
Section: Introductionmentioning
confidence: 99%